2011
DOI: 10.2147/gictt.s18423
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic role of cytokines in colon cancer

Abstract: In the United States, colorectal cancer (CRC) is the third most common cancer diagnosis in both men and women. Many patients are diagnosed with advanced stage CRC which has a high rate of mortality compared to localized CRC. Developing novel diagnostic tools is important for early detection to decrease both morbidity and mortality. Currently, colonoscopy is the most common screening test, though its effectiveness in reducing mortality remains uncertain and it is costly, invasive and carries risk. Stool-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(104 reference statements)
1
2
0
Order By: Relevance
“…Schetter et al [43] also reported that IL-1B was highly expressed in adenocarcinoma tissue compared with normal tissue in CRC patients. Furthermore, some studies revealed that high expression levels of IL-1B were signi cantly associated with tumor staging, survival, and metastasis in CRC patients [44][45]. In the present study, we also found that the expression level of IL-1B was higher in tumor tissue than normal tissue.…”
Section: Discussionsupporting
confidence: 79%
“…Schetter et al [43] also reported that IL-1B was highly expressed in adenocarcinoma tissue compared with normal tissue in CRC patients. Furthermore, some studies revealed that high expression levels of IL-1B were signi cantly associated with tumor staging, survival, and metastasis in CRC patients [44][45]. In the present study, we also found that the expression level of IL-1B was higher in tumor tissue than normal tissue.…”
Section: Discussionsupporting
confidence: 79%
“…TNF-α signaling promotes the expression of downstream inflammatory mediators associated with abnormal cell proliferation and differentiation. 32 An elevated TNF-α level increased the risk of CRC, 33 and a decreased IL-1β level reduced the risk of advanced CRC. 34 IL-6, an important downstream inflammatory mediator of TNF-α signaling pathway, is associated with tumor occurrence, tumor size, advanced tumor stage and the survival of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the activation of a cytokine pathway associated with inflammation or disease progression, their concentration can increase up to 1,000-fold ( 22 ). The role of cytokines as potential biomarkers in cancer has been investigated by many studies ( 23 26 ) including our group ( 27 , 28 ). Some cytokines are excessively produced by tumor cells ( 29 ), and consequently, varying cytokine concentrations seem to be valid predictors for disease progression and the effects of treatment ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%